Tachydromia maculipennis Walker 1849 ... - Shamshev, Igor V.; Grootaert, Patrick (Zenodo, 2024)
Tachydromia maculipennis Walker (Fig. 10) Tachydromia maculipennis Walker, 1849: 507. Type locality: Canada, St. Martin’s Falls, Albany River, Hudson’s Bay (after Smith 1971: 367). Tachypeza pusilla Loew, 1864b: 87 [Cent. 5, no. 74]. Type locality: USA, Illinois. Tachydromia pusilla (Loew): Melander, 1910: 52 (synonymy). Phoneutisca bimaculata Loew: Melander, 1902: 204. Misidentification. Type material examined. Smith (1971: 367) provided data about the holotype of this species, which is represented only by two legs. Data on the syntype of Tachypeza pusilla Loew (including photos of labels and habitus) are available from the database of insect primary types in the collection of MCZ (https://mczbase.mcz.harvard.edu/ guid/ MCZ:Ent:1168). Additional material examined. CANADA. Manitoba: Aweme, 14.vi.1924, R.D. Bird (2 ♂, 2 ♀, CNC); 2 mi. W Stockton, 26.v.1958, C.D.F. Miller (1 ♂, CNC); 5 mi. SW Chilo, ex choke-cherry, floodplain community nr. Tamarack Bog, 5.vi.1958, J.F. McAlpine (1 ♂, 7 ♀, CNC); 2 mi. W ... : Published as part of Shamshev, Igor V. & Grootaert, Patrick, 2024, Revision of the described Nearctic species of the genus Tachydromia Meigen (Diptera: Hybotidae), pp. 151-196 in Zootaxa 5403 (2) on pages 172-175, DOI: 10.11646/zootaxa.5403.2.1, http://zenodo.org/record/10561768 ...